A study of waist circumference, waist-hip ratio as markers of type 2 diabetes mellitus and their correlation with family history of diabetes - Gokhale, Vijayashree S.; Jagdale, Nilesh; Batra, Tanvi; Gulati, Shipra (International Journal of Research in Medical Sciences, 2016)
Background: Type 2 Diabetes, is almost an ‘epidemic’ in India. A lot has to be done to prevent or at least postpone its onset. Hence finding bio-markers is important to warn people and create awareness. In India people pay a lot of importance to Family History, and though a positive family history, may predict Diabetes, we wanted to study its correlation to other bio-markers. Methods: Waist circumference, Waist hip ratio was measured in 184 Type 2 Diabetes patients .And history of Diabetes in mother, father or both was recorded .Data tabulated and subjected to statistical analysis. Results: Of the total number (n=184) type 2 diabetes patients studied, males were 93, females 91. 74.2 % males and 83.5 % females had a waist circumference above cut-off (90 cms for males and 80cms for females). 35 males and 42 females had a family history of diabetes. Of these, Father was diabetic in 16 males and 16 females, while mother was diabetic in 19 males and 26 females. Conclusions: Waist circumference and waist hip ratio above cut-off values emerged as common positive findings in majority of type 2 diabetic patients. Family history, individually as Paternal or Maternal Diabetes did not show statistically significant correlation with waist circumference or Waist-hip ratio.